Cancer Therapy-Induced Cardiotoxicity: Where are We Now? - Guertin, Pierre A. (Cardiology and Cardiovascular Medicine, 2017)
Cardiotoxicity effects, cardiovascular diseases (CVDs), and hypertension occurring months to several years postchemotherapy and/or radiotherapy are well-recognized by experts. Anthracyclines were found in the late 1960s to be dose-dependently associated with induced-cardiotoxicity, often leading to cardiomyopathy and cardiac failure. Since then, epidemiologic research has led to some advances, although pivotal questions about global incidence, populations at risk, cellular mechanisms, and preventive treatments remain either incompletely understood or unaddressed. For instance, the incidence of cancer-surviving patients who die of cardiac failure after chemotherapy and/or radiotherapy is still a subject of debate - for reasons that are unclear, available statistics vary significantly from one epidemiology study to another. Moreover, no safe cardioprotective agents have yet been fully endorsed and approved by regulatory agencies for prevention or treatment of this specific medical problem. A drug called dexrazoxane was initially approved by the US Food and Drug Administration and the European Medicines Agency, but a restricted use notice was released in 2011 since several cases of secondary acute myeloid leukemia and myelodysplactic syndrome had been reported. As of today, hematologists and cardiologists remain generally reluctant to recommend dexrazoxane or other cardioprotective drugs (off-label prescription), probably because of unclear risks and lack of evidence-based medicine. Questions about unexpected adverse events or drug-drug interaction issues reducing the efficacy of specific chemotherapies also need to be addressed.